Corruption and Bad Policies Repel Foreign Capital and Cause Domestic Capital to Flee: Is Jovanovic Right? - Tyavambiza, Takawira (International Journal of Economics and Financial Issues, 2017)
Corruption in Zimbabwe has made the country’s economic system too porous to handle investments of note while protecting and enriching those responsible for the damage. As a result, productive capital in the hands of foreign direct investors and also domestic capital has fled the country. In addition to the capital haemorrhage, corruption has also made it impossible for the country to attract new foreign direct investment as investors redirect their investments to other friendly destinations. Combating corruption is possible though eliminating it is not. The cost of corruption in repelled foreign capital and capital flight can never be quantified. The country is, however, counting the losses in cumulative amounts reported in various corruption cases, with the estimated US 15billion loss on domestic resource in form of diamonds only being the highest. For a country with an annual fiscal budget of just about US4billion, such losses are substantial. The only recommendation from this discussion is that it all ends with the Government to start doing something as the ultimate centre of power in the land. Without a corrective and penalizing voice from the Government, which is backed by action, fighting corruption shall remain a life time dream for many sober Zimbabweans who have never tested the sweetness of discretionary power. Unless and until something about corruption is done at the highest level, Zimbabwe will remain a living testimony of Jovanovic’s assertion that corruption repels foreign capital and causes domestic capital to flee. Keywords: Corruption, economic growth, capital flight, bureaucratic power, public office, Zimbabwe. JEL Classifications: D73, F21, F43